2016
DOI: 10.1590/1413-81232015212.20182014
|View full text |Cite
|
Sign up to set email alerts
|

Estudos de avaliação do conhecimento nutricional de adultos: uma revisão sistemática

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 38 publications
4
31
1
18
Order By: Relevance
“…Regarding marital status, unlike previous studies, individuals who were married had a higher score on dietary knowledge and better dietary guideline awareness. That may be due to the fact that people who are married are most likely to share their nutrition information with each other [17]. This study confirmed the findings from previous studies that women had a higher dietary knowledge than men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding marital status, unlike previous studies, individuals who were married had a higher score on dietary knowledge and better dietary guideline awareness. That may be due to the fact that people who are married are most likely to share their nutrition information with each other [17]. This study confirmed the findings from previous studies that women had a higher dietary knowledge than men.…”
Section: Discussionsupporting
confidence: 91%
“…A great number of variables are available in the CHNS. Referring to previous nutrition studies, some demographic, socioeconomic, residential area and health education intervention variables were associated with nutritional knowledge [9,10,17,18]. Since this study was designed to explore the contribution of socioeconomic factors on dietary knowledge inequality, we constructed a hypothesis that all the socioeconomic variables and potential control variables in the CHNS are all associated with dietary knowledge.…”
Section: Independent Variablesmentioning
confidence: 99%
“…An adequate methodological quality was assessed according to a consistency with 50% or more of the items in the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) Statement as Barbosa, Vasconcelos, Correia, & Ferreira 14 and Silva, Lyra, & Lima 15 used in their studies. …”
Section: Methodsmentioning
confidence: 99%
“…To assess the sensitivity of results to the composition of nutrition knowledge questions, we separate indexes for behaviour and mechanism knowledge questions. We also tested additional measures using all 42 variables, following the most common approach found in the literature (e.g., Barbosa et al, 2016;Block, 2004;Debela et al, 2017;Karmacharya et al, 2017;Kigaru, Loechl, Moleah, & Ndungu, 2016;Mbuya, Menon, Habicht, Pelto, & Ruel, 2013), and also strict adherence to the Trakman et al (2017) criterion that 20-80% of respondents answer correctly, with no significant differences from the results shown.…”
Section: Measures Of Nutrition Knowledgementioning
confidence: 99%
“…Additionally, this literature tends to focus on overnutrition whereas nutrition concerns in developing countries also include undernutrition of all forms, hygiene and care practices, and food safety (Barbosa, Vasconcelos, dos Santos Correia, & Ferreira, 2016).…”
mentioning
confidence: 99%